Development and Psychometric Evaluation of a Brief Approach and Avoidance of Alcohol Questionnaire. (15th January 2019) - Levine, Jacob A.; Noyes, Emily T.; Gius, Becky K.; Ahlich, Erica; Rancourt, Diana; Houston, Rebecca J.; Schlauch, Robert C.
Abstract : Background: The Approach and Avoidance of Alcohol Questionnaire (AAAQ) was developed as a measure of craving to assess both desires to consume and desires to avoid consuming alcohol. Although the measure has been used in a variety of populations to predict future alcohol use behavior, the factor structures observed vary based on sample type (e.g., clinical vs. college samples) and may be overly long for use in repeated measures designs. The current article describes the development of a brief version of the AAAQ for use in clinical populations. Methods: Using existing data sets of individuals in treatment for alcohol use disorder, exploratory analyses (e.g., exploratory factor analysis and item response theory) were conducted using an inpatient sample ( N  =   298) at a substance abuse treatment facility. Confirmatory analyses (e.g., confirmatory factor analysis and multiple regression) were conducted using an inpatient detoxification sample ( N  =   175) and a longitudinal outpatient treatment sample ( N  =   53). Results: The brief AAAQ had comparable internal consistency, explained a similar amount of variance in alcohol consumption and related problems, and exhibited superior model fit as compared to the original measure. Conclusions: These findings indicate that the brief AAAQ is an effective tool to assess alcohol craving in clinical populations in treatment settings. Abstract : We describe the development and validation of a brief 6‐item measure used to evaluate motivations to approach and avoid alcohol. This brief version of the measure performs similarly to the longer original measure, demonstrating similar variance accounted for in alcohol consumption and related problems, internal consistency, and predictive validity. Given the brief nature of the measure, it is appropriate for use in time limited situations, including repeated measures and ecological momentary assessment.